The Evolution of the Definition of Crimes against Humanity under International Criminal Law - Hoffmann, Tamás (The ICC at 25: Lessons Learnt, 2025)
The evolution of the definition of crimes against humanity under international criminal law reflects a significant shift in the treatment of civilian populations by states, transitioning from a domain reserved for state discretion to one governed by international law. This chapter traces the historical development of the concept, beginning with 19th-century articulations of the principle of humanity, through its codification in the Nuremberg Charter post-World War II, to its current status under the Rome Statute of the International Criminal Court (ICC).Initially, the principle of humanity was invoked in the context of war and humanitarian law. However, it wasn't until the atrocities of World War I, particularly against Armenians, that the term "crimes against humanity" emerged, leading to the first international legal accountability efforts.The Nuremberg Trials marked a pivotal moment, defining crimes against humanity as acts committed against civilian populations in connection with war crimes. This definition initially required a nexus to armed conflict, a requirement that has evolved over time. Subsequent tribunals, such as the ICTY and ICTR, expanded the scope of these crimes, allowing for prosecution in peacetime and clarifying the contextual elements necessary for establishing such crimes.The Rome Statute further codified these developments, defining crimes against humanity as acts committed as part of a widespread or systematic attack against civilians, without necessitating a link to armed conflict. Despite this progress, ambiguities remain regarding the interpretation of "other inhumane acts" and the necessity of state or organizational policy. The ongoing discourse around these issues highlights the dynamic nature of international criminal law and its capacity to adapt to emerging global challenges, underscoring the importance of crimes against humanity in addressing future injustices. Keywords: Crimes against humanity, Martens Clause, Nuremberg Tribunal, ICC, ICTY